Minister Decree No. 33/2017 Amending Some Provision of the Executive Regulations of the Law on Capital market Issued by Decree of the Minister of Economy and Foreign Trade No. 135 of the year 1993 = قرار وزاري رقم 33 لسنة 2017 بتعديل بعض أحكام اللائحة التنفيذية لقانون سوق المال الصادرة بقرار وير الاقتصاد والتجارة الخارجية رقم 135/1993 - Egypt. Minister Prime (2025)
Ministry of investment and international cooperation Decree no. 33 of the year 2017 amending some provisions of the executive regulations of the law on capital market issued by decree of the minister of economy and foreign trade no. 135 of the year 1993 وزارة الاستثمار والتعاون الدولى قرار رقم 33 لسنة 2017 بتعديل بعض أحكام اللائحة التنفيذية لقانون سوق المال الصادر بقرار وزير الاقتصاد والتجارة الخارجية رقم 135 لسنة 1993